2008
DOI: 10.1158/1535-7163.mct-07-0381
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of drug resistance by artificial transcription factors

Abstract: The efficiency of chemotherapeutic treatments in cancer patients is often impaired by the acquisition of drug resistance. Cancer cells develop drug resistance through dysregulation of one or more genes or cellular pathways. To isolate efficient regulators of drug resistance in tumor cells, we have adopted a genome-wide scanning approach based on the screening of large libraries of artificial transcription factors (ATFs) made of three and six randomly assembled zinc finger domains. Zinc finger libraries were li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Study also confirmed ZNF217 could promote tumor progression by accelerating ovarian cancer cell proliferation and invasion [9]; ZBP-89, a member of the Krüppel family, was related to distant metastasis and prognosis of renal cell carcinoma [10]. There were other studies that confirmed that the artificial transcription factor could be used for the detection of resistance genes and pathways, which might reverse the drug tolerance of tumors [11]. But there had been no report on relationship between ZNF139 and metastasis of gastric cancer cell in migration and invasion ability.…”
mentioning
confidence: 80%
“…Study also confirmed ZNF217 could promote tumor progression by accelerating ovarian cancer cell proliferation and invasion [9]; ZBP-89, a member of the Krüppel family, was related to distant metastasis and prognosis of renal cell carcinoma [10]. There were other studies that confirmed that the artificial transcription factor could be used for the detection of resistance genes and pathways, which might reverse the drug tolerance of tumors [11]. But there had been no report on relationship between ZNF139 and metastasis of gastric cancer cell in migration and invasion ability.…”
mentioning
confidence: 80%
“…Early work on the use of engineered zinc-finger transcription factors revealed that synthetic transcriptional modulators are effective tools for a broad range of applications, enabling such tasks as inhibiting viral replication (Papworth et al 2003;Reynolds et al 2003;Segal et al 2004;Eberhardy et al 2006), modulating the expression of disease-associated loci (Graslund et al 2005;Wilber et al 2010), inducing angiogenesis for accelerated wound healing (Rebar et al 2002), and genomic screening of cellular targets for cancer progression and drug resistance Blancafort et al 2005Blancafort et al , 2008. Facilitated by many of the insights gained from zinc-finger transcription factor technology, both TALEs and CRISPR-Cas9 have now further expanded the possibilities of engineered transcriptional activators and repressors.…”
Section: Applications Of Targeted Transcriptional Regulationmentioning
confidence: 99%
“…Biomedicine: Nanoparticles mediated drug delivery systems, xenotransplantation, gene therapies, control and prevention of genetic diseases [25].…”
Section: Crops and Livestockmentioning
confidence: 99%